Study of the Characteristics and Photocatalytic Application of ZnO Nanoparticles Synthesized by Cold Plasma - MESSAI Ridha (University Eloued جامعة الوادي, 2024)
This thesis explores the synthesis, characterization, and photocatalytic applications of zinc oxide nanoparticles (ZnO NPs) produced using a Gliding Arc Discharge (GAD) plasma method. The study primarily investigates the influence of discharge duration on the structural, optical, and photocatalytic properties of ZnO NPs. Characterization techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-visible spectroscopy were employed to evaluate the physical and chemical properties of the nanoparticles. The results show that increasing from 10 min to 60 min the discharge duration leads to a decrease in particle size from 28 nm to 25 nm, higher band gap energies, and improved thermal stability. The ZnO NPs exhibited excellent photocatalytic performance in the degradation of organic pollutants, with degradation efficiencies of 92.9%, 71%, and 88% for Brilliant Cresyl Blue (BCB), Methylene Blue (MB), and Congo Red (CR) dyes, respectively, under UV light. Furthermore, under sunlight, the ZnO NPs achieved up to 97% photodegradation efficiency of CR dye after 150 minutes, with optimal performance at pH 8. The study also demonstrated the effectiveness of combining GAD plasma with ZnO NPs for aspirin degradation, achieving a 96.72% degradation efficiency within 90 minutes. These findings highlight the potential of GAD plasma-synthesized ZnO NPs for practical applications in wastewater treatment, offering a sustainable and efficient solution for organic pollutant degradation. The synthesized ZnO NPs also demonstrated stability and reusability over multiple cycles, showcasing their potential for large-scale environmental applications تستكشف هذه الأطروحة توليف وتوصيف وتطبيقات التحفيز الضوئي لجسيمات أكسيد الزنك النانوية (ZnO NPs) التي تم إنتاجها باستخدام طريقة تفريغ القوس المنزلق (GAD). تركز الدراسة بشكل رئيسي على تأثير مدة التفريغ على الخصائص الهيكلية والبصرية والتحفيزية الضوئية لجسيمات أكسيد الزنك. تم استخدام تقنيات التوصيف مثل حيود الأشعة السينية (XRD) والمجهر الإلكتروني الماسح (SEM) والمطيافية فوق البنفسجية المرئية لتقييم الخصائص الفيزيائية والكيميائية للجسيمات النانوية. أظهرت النتائج أن زيادة مدة التفريغ من 10 دقائق إلى 60 دقيقة تؤدي إلى تقليل حجم الجسيمات من 28 نانومتر إلى 25 نانومتر وزيادة طاقة فجوة النطاق وتحسن الاستقرار الحراري. أظهرت جسيمات ZnO NPs أداءً ممتازًا في تحفيز التحلل الضوئي للملوثات العضوية، حيث بلغت كفاءة التحلل 92.9٪ و71٪ و88٪ لأصباغ أزرق الكريسيل اللامع والميثيلين الأزرق وأحمر الكونغو على التوالي تحت ضوء الأشعة فوق البنفسجية. علاوة على ذلك، حققت الجسيمات النانوية ZnO كفاءة تصل إلى 97٪ في التحلل الضوئي لصبغة CR تحت أشعة الشمس بعد 150 دقيقة، مع أداء مثالي عند درجة حموضة pH 8. كما أظهرت الدراسة فعالية الجمع بين تفريغ القوس المنزلق وجسيمات ZnO في تحلل الأسبرين، حيث تم تحقيق كفاءة تحلل بلغت 96.72٪ في غضون 90 دقيقة. تُبرز هذه النتائج إمكانيات جسيمات ZnO NPs المُصنّعة باستخدام تفريغ القوس المنزلق في التطبيقات العملية لمعالجة مياه الصرف، مما يوفر حلاً مستدامًا وفعالًا لتحلل الملوثات العضوية. كما أظهرت الجسيمات النانوية المُصنّعة استقرارًا وإمكانية إعادة الاستخدام على مدار دورات متعددة، مما يعزز إمكانياتها في التطبيقات البيئية واسعة النطاق.
Thèse de Doctorat
Keywords: ZnO Nanoparticles; Gliding Arc Discharge Plasma; Photocatalysis; Organic Pollutants; Aspirin Degradation; Water Purification; Nanomaterials; جسيمات أكسيد الزنك النانوية; تفريغ القوس المنزلق بالبلازما; التحفيز الضوئي; الملوثات العضوية; تحلل الأسبرين; تنقية المياه; المواد النانوية